Fluoro-deoxy-glucose uptake in the mylohyoid muscle: a common misconception. Issue 5 (May 2020) - Pizzuto, Daniele A.; Husmann, Lars; Stolzmann, Paul; Meerwein, Christian; Orita, Erika; von Schulthess, Gustav K.; Huellner, Martin W.
Abstract : Aim: The mylohyoid muscle is often believed to exhibit high physiologic fluoro-deoxy-glucose (FDG) uptake. Aim of this study was to use PET/MR for adequately assessing the normal FDG distribution in floor of the mouth (FOM) muscles and neighboring major salivary glands. Materials and methods: Patients scanned with a simultaneous PET/MRI system for initial staging or follow-up of head and neck tumors, with no malignant lesions in salivary glands or in FOM, were included. Volumes-of-interest (VOIs) were positioned separately for bilateral mylohyoid, digastric, genioglossus, and geniohyoid muscles, based on T2-weighted and T1-weighted images, and for bilateral parotid, submandibular, and sublingual glands in the same way. SUVmax was measured for each VOI. Results: Six hundred and ninety-two VOIs were positioned. FDG uptake in mylohyoid (SUVmax  = 1.94 ± 0.37) and digastric muscles (SUVmax  = 2.01 ± 0.37) were significantly higher compared to that in geniohyoid (SUVmax  = 1.67 ± 0.53) and genioglossus muscles (SUVmax  = 1.75 ± 0.54) (Friedman's test; P  < 0.001). FDG uptake in the sublingual glands (SUVmax  = 3.77 ± 1.63) was significantly higher compared to the parotid glands (SUVmax  = 2.34 ± 0.60) and submandibular glands (SUVmax  = 2.51 ± 0.59) (Wilcoxon signed-ranks test; P  < 0.001). FDG uptake in sublingual glands was significantly higher than FDG uptake in the mylohyoid muscles ( P  < 0.001). FDG uptake in the parotid, submandibular, and sublingual glands was inversely correlated to the age of subjects (Spearman' rho coefficient: –0.397/ P  = 0.004; –0.329/ P  = 0.021; –0.535/ P  < 0.001, respectively). Conclusion: The sublingual glands yield the highest physiologic FDG uptake in the FOM. High FDG uptake in the mylohyoid muscle is a common misconception.